Analysis of the impact of economic changes in the overall economic growth in Iraq for the period (1995- 2020) (Entrepreneurship Journal for Finance and Business, 2022)
This research aims to highlight the role of macro-economic variables in achieving economic growth in Iraq, relying on the Eviews10 program.  The results of the research showed an inverse relationship between the net foreign operations in the inflation rate, the broad money supply, the long term, with the gross domestic product, and a direct relationship between each of the net foreign operations.  In the short term, the broad money supply with the gross domestic product, and a direct relationship between the broad money supply, the exchange rate, the budget deficit in the two terms, with the gross domestic product.